Síntese e caracterização de KNbO3 aplicado na fotodegradação remazol amarelo ouro em solução fotodegradação de remazol amarelo ouro em solução aquosa aquosa - Silva, Arnayra Sonayra de Brito (2014)
The potassium niobate, KNbO3, of orthorhombic perovskite presenting ferroelectric, optical property, in addition to their use in heterogeneous photocatalysis. This work consists of two stages - the synthesis of potassium niobate and its evaluation in the photodegradation of the dye Remazol Yellow Gold (RNL). The synthesis of KNbO3 was performed by polymeric precursors and catalysts were characterized by X- ray diffraction ( XRD ), infrared spectroscopy (IR) spectroscopy, ultraviolet visible (UV-Vis) region and area analysis surface . XRD results showed that the perovskite had a far-reaching organization, and there was a decrease in the secondary phase (K4Nb6O17). IR spectra confirmed these data by presenting a reduction of the bands related to vibrations with short double bond character of the Nb = O. The surface area values were lower with increasing temperature. The photocatalyst was applied to the dye Remazol yellow discoloration of gold (RNL) and the parameters used were: radiation time (2 and 4 h), the amount of catalyst (5 or 20 mg) and the change in pH (3 and 6). It was observed that a higher radiation time, a smaller quantity of catalyst and lower pH favoring a better photocatalytic efficiency, obtaining a result of discoloration of 55 %. A comparative study was done with a temperature of 700 º C, as the best result obtained in the previous tests, and observed a photocatalytic efficiency of 67% discoloration.